2019
DOI: 10.1038/s41598-019-43219-1
|View full text |Cite
|
Sign up to set email alerts
|

8.2 ka event North Sea hydrography determined by bivalve shell stable isotope geochemistry

Abstract: The abrupt 8.2 ka cold event has been widely described from Greenland and North Atlantic records. However, its expression in shelf seas is poorly documented, and the temporal resolution of most marine records is inadequate to precisely determine the chronology of major events. A robust hydrographical reconstruction can provide an insight on climatic reaction times to perturbations to the Atlantic Meridional Overturning Circulation. Here we present an annually-resolved temperature and water column stratificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The end of the early Holocene is marked by a large-scale Northern Hemisphere cooling event initiated by an abrupt drainage of Lake Agassiz into the North Atlantic that weakened Atlantic Meridional Overturning Circulation, and is 305 well documented in many records (Thomas et al, 2007;Matero et al, 2017;Estrella-Martínez et al, 2019;Voarintsoa et al, 2019). Although this is a globally well described event, relatively few records (fewer than 10 records reviewed in this paper) from the Northeastern Pacific and Western United States record impacts of this event.…”
Section: 2 Ka Eventmentioning
confidence: 98%
“…The end of the early Holocene is marked by a large-scale Northern Hemisphere cooling event initiated by an abrupt drainage of Lake Agassiz into the North Atlantic that weakened Atlantic Meridional Overturning Circulation, and is 305 well documented in many records (Thomas et al, 2007;Matero et al, 2017;Estrella-Martínez et al, 2019;Voarintsoa et al, 2019). Although this is a globally well described event, relatively few records (fewer than 10 records reviewed in this paper) from the Northeastern Pacific and Western United States record impacts of this event.…”
Section: 2 Ka Eventmentioning
confidence: 98%
“…While some research has found that more rapid variations in seawater d 18 O values have occurred due to catastrophic, largescale events such as the 8.2kyr event (e.g. Estrella-Martínez et al, 2019a), the MCA has not been shown to be one of these events. Accordingly, as there has been no significant global glaciation between the MCA and the present, it is assumed that the modern global seawater d 18 O values are analogous to those of the MCA.…”
Section: Influences On the Isotope Geochemistry Of Shellsmentioning
confidence: 99%
“…well documented in many records (Thomas et al, 2007;Matero et al, 2017;Estrella-Martínez et al, 2019;Voarintsoa et al, 2019). Although this is a globally well described event, relatively few records (fewer than 10 records reviewed in this paper) from the Northeastern Pacific and Western United States record impacts of this event.…”
mentioning
confidence: 77%